Actuality of Agricultural Loss and Agricultural Production (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Actuality of losses size of agricultural and forestry production deposit total today. Losses size of agricultural and forestry production that are subject to reimbursement, is stated in order determined by the decree of the Cabinet of Ministers of Ukraine №1279 from 17.11.1997. From the time the decree was adopted more than 18 years have passed. The article proposes the mechanism of indexation of losses norms of agricultural and forestry production aspreconditions of improving economic mechanism of regulation of urbanization of productive lands and earnings to additional payments to local budgets, that will be directed to improving and lands protection.
Keywords: agricultural lands, agricultural production, arable land, hayfields, pastures